Between points and rights guarded: the scientific production special educaction in the UVA-Sobral-CE pedagogy course - Nascimento, Wildiane Gonçalves do; Vieira, Railane Bento; Soares, Ana Cristina Silva; da Silva, Rejane Maria Gomes; Miranda Pinto, Francisco Ricardo (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This study focuses on Special Education as a possibility to ensure the rights guarded by the official documents. It is aimed to explore the scientific production of the Pedagogy course from the State University of Vale do Acaraú concerning the Special Education and the study area. The contemplated literature seeks to contextualize the emergence of Special Education from the theorists Capellini; Mendes (2005), Rosseto; Tureck (2005) and Bruno (2006), emphasizing the context and discourses on Special Education in the Official Documents supported by Brasil (1994), UNESCO (1990), Brasil (1996), Brasil (2012), Brasil (2015), among others. This study was carried out by means of a qualitative approach, using an integrative literature review conducted in the Pedagogy course of the aforesaid university and had the research group História e Memória Social da Educação e da Cultura (MEDUC) as locus, in which seventeen articles of this group collection  were analyzed. The results show the complexity and importance in discussing this issue among professionals of this field, while it was concluded that even with the existence of laws providing rights of inclusion, children with disabilities are still being excluded in their own environment.